Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1186/s13613-019-0539-2
|View full text |Cite
|
Sign up to set email alerts
|

Candidemia in critically ill immunocompromised patients: report of a retrospective multicenter cohort study

Abstract: Background Immunocompromised critically ill patients constitute a population with the high risk of candidemia. This retrospective study aimed to assess the outcome of immunocompromised critically ill patients with candidemia. Secondary objectives were to describe clinical phenotypes of these patients, Candida ecology, and factors associated with mortality. Results Overall, 121 patients were included in this study. Median delay from candidemia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 22 publications
8
27
0
1
Order By: Relevance
“…to specific antifungal drugs may not necessarily correlate with outcome. Ghrenassia and colleagues observed that Candida susceptibility was not associated with survival after candidemia in immunocompromised patients [21]. Neither was the choice of antifungal agent in favor of echinocandins.…”
Section: Discussionmentioning
confidence: 99%
“…to specific antifungal drugs may not necessarily correlate with outcome. Ghrenassia and colleagues observed that Candida susceptibility was not associated with survival after candidemia in immunocompromised patients [21]. Neither was the choice of antifungal agent in favor of echinocandins.…”
Section: Discussionmentioning
confidence: 99%
“…C. albicans is an opportunistic pathogen of global clinical significance [ 48 , 49 , 50 ]. Preventing biofilm formation and eradicating existing biofilms is important to reduce mortality rates of infections caused by these microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, a multi-center study has shown that the mortality rate significantly increased for every hour delayed in diagnosis of candidemia (2). Rapid diagnosis of candidemia is even more crucial in immunocompromised patient populations because of a higher mortality rate in this patient group (3,4). Conventional culture-based identification methods lack the speed needed to aid in choosing the appropriate antifungal drugs for timely management of patients suffering from these invasive fungal infections.…”
Section: Introductionmentioning
confidence: 99%